2015
DOI: 10.7202/1030397ar
|View full text |Cite
|
Sign up to set email alerts
|

Impact of export support: a conceptual model for export start-ups1

Abstract: Les Export Start-Ups sont un type d’entreprise à internationalisation précoce qui recèle un fort potentiel de croissance et d’emploi. Néanmoins, elles sont fragilisées par leur manque de ressources et sont nombreuses à échouer sur les marchés étrangers. En nous appuyant sur la Théorie des Ressources, nous posons alors la question de l’efficacité des Services d’Accompagnement à l’Export (SAE) à fournir à ces entreprises les ressources manquantes pour performer sur les marchés étrangers, alors même que ces servi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 117 publications
0
12
0
1
Order By: Relevance
“…Three variables that dominate are: workforce size, export volume or turnover abroad and international experience/presence. Specific actors are observed such as 'born globals' by Catanzaro et al, 2015) or novel typologies are created such as that by Freixanet (2012); different categorisations have been developed to describe the export development stages of firms with differing segmentation. Freixanet (2012) considers four elements of segmentation: level of internationalisation involvement and skills using criteria such as export volume, size of the export department, creation of permanent establishments abroad and creation of production subsidiaries.…”
Section: Internationalisation Support Servicesmentioning
confidence: 99%
See 2 more Smart Citations
“…Three variables that dominate are: workforce size, export volume or turnover abroad and international experience/presence. Specific actors are observed such as 'born globals' by Catanzaro et al, 2015) or novel typologies are created such as that by Freixanet (2012); different categorisations have been developed to describe the export development stages of firms with differing segmentation. Freixanet (2012) considers four elements of segmentation: level of internationalisation involvement and skills using criteria such as export volume, size of the export department, creation of permanent establishments abroad and creation of production subsidiaries.…”
Section: Internationalisation Support Servicesmentioning
confidence: 99%
“…The combinations of time to internationalisation, stages and point in time establish strong theoretical foundations for explaining variety in SME internationalisation processes. However, despite the abundant literature, investigations of the role of support services are rare (Catanzaro et al, 2015; Kazlauskaitė et al, 2015), particularly for distant countries. For example, a few studies cite the performance of export promotion services (Freixanet, 2012) and perceptions of their usefulness (Lederman et al, 2010), but there appears to be little research investigating how agents and organisations can help SMEs throughout their internationalisation process.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…This point is all the greater since Nummela et al (2004) found that the success of internationalization missions was linked to the global mindsets of managers (heavily influenced by their attitudes). This theme could also be a module to complement the initiatives already in place in the accompanying structures (Catanzaro, Messeghem & Sammut, 2013). !…”
Section: Discussion and Conclusion !mentioning
confidence: 99%
“…Dans le second cas, ils résultent de la volonté d'une entreprise (ou d'un individu) de fédérer un nombre défini d'acteurs pour une durée limitée en vue de répondre à un but précis (Thévenard-Puthod & Picard, 2013). Ces réseaux sont alors qualifiés de « calculatoires » (Catanzaro, Messeghem & Sammut, 2012) puisqu'ils regroupent un ensemble d'acteurs motivés à poursuivre les relations au regard des coûts/ bénéfices associés à leur engagement au sein du réseau (Styles et al, 2008). Dès lors, le sentiment d'appartenance et la motivation à s'engager et à maintenir les connexions seront différents selon la nature du réseau.…”
Section: Sentiment D'appartenance Socialisation Et éChange D'informaunclassified